PENGARUH LEVERAGE, PROFITABILITAS, LIKUIDITAS, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN - Dwi Ayu Paradita; Hesty Ervianni Zulaecha; Imam Hidayat; Dewi Rachmania (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study is to determine the effect of leverage, profitability, liquidity, managerial ownership, and institutional ownership on dividend policies in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research period used is 5 years, namely the period 2015-2019. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. The sampling technique uses purposive sampling technique. Based on the established criteria obtained 7 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that institutional ownership has a significant positive effect on dividend policy, managerial ownership has a significant negative effect on dividend policy. Leverage, profitability, and liquidity have no significant influence on dividend policy. Leverage, profitability, liquidity, managerial ownership, and institutional ownership together affect dividend policy